IDENTITY PERSPECTIVES - S. M. Khenkin (MGIMO University Press, 2018)
Book Review. Identity. Personality, Society, Politics. Encyclopedic Edition. Ed. by I.S. Semenenko. Moscow: Ves Mir Publishers, 2017. 992 p. (In Russian).The Encyclopedic Edition represents a seminal volume devoted to the research of the present-day scientific discourse on the problems of identity and the practical application of this category to explanation of social reality. The authors view the problems of identity from various perspectives, focusing on the conceptual meaning, main types and dimensions, methodological approaches and research methods, portraits of scholars studying identity at different times. Dozens of leading scholars from academic institutions and university centers of Russia contributed to the publication.